Effect of growing media and fertilizers on the early growth of Aechmea fasciata Bak - D'Andréa, J. C. [UNESP]; Demattê, M. E. S. P. [UNESP] (International Society Horticultural Science, 2000)
Mixtures of tree fern fiber, coconut bark, pine bark, sugarcane bagasse, broken pieces of clay pots, vermiculite and humus were compared as substrates for Aechmea fasciata cultivation. These substrates were combined with the following fertilization methods: A1 = NPK applied on leaves during the first growing phase, and on leaves and substrates later; A2 = commercial product with macro and micronutrients, and 9% of aminoacids, applied on substrate; A3 = A1 = A2; A4 = control without fertilization. Evaluations until 260 days after planting showed that the mixture composed by 45% coconut bark + 45% pine bark + 10% humus may be recommended to substitute tree fern fiber, extracted from endangered species. The best fertilization methods were A1 and A3.
Keywords: Aechmea fasciata; Bromeliaceae; fertilization; growing media